The land before time V : the mysterious island (CA : Universal Home Video, 1990)
In their search for a new home after a cloud of "Swarming Leaf Gobblers" devours the plants in the Great Valley, Littlefoot, Cera, Spike, Ducky and Petrie cross the Big Water to a mysterious island where they become reacquainted with Chomper, a young Sharptooth.